2020
DOI: 10.1186/s12866-020-01776-w
|View full text |Cite
|
Sign up to set email alerts
|

Silver diamine fluoride (SDF) used in childhood caries management has potent antifungal activity against oral Candida species

Abstract: Background: The microbiome of Severe-Early Childhood Caries (S-ECC), is characterized by an ecosystem comprising bacterial and fungal species, with a predominance of Candida species. Hence, an anti-cariogen effective against both bacteria and fungi would be valuable in the management of S-ECC. Here we evaluate the antifungal effect of silver diamine fluoride (SDF) against 35-clinical yeast isolates (Ten-each of C. albicans, C. krusei, C. tropicalis and five C. glabrata strains) from dentinal caries-lesions fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
14
0
2
Order By: Relevance
“…On the other hand, silver ions act directly against bacteria in lesions by breaking membranes, denaturing proteins, and inhibiting DNA replication (7,14,16). A recent study also showed the antifungal potency of SDF (27).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, silver ions act directly against bacteria in lesions by breaking membranes, denaturing proteins, and inhibiting DNA replication (7,14,16). A recent study also showed the antifungal potency of SDF (27).…”
Section: Discussionmentioning
confidence: 99%
“…Silver has extracellular and intracellular binding properties. Therefore, this molecule has the ability to bind to the microbial wall and, once it enters the cell, to bind to and damage proteins, genetic material or denature cytoplasmic enzymes, among other effects [21,22]. Additionally, this type of dendron also binds to the negatively charged cell membranes due to electrostatic interactions causing destabilization of the membrane, enhancing its effectiveness against established biofilms.…”
Section: Combined Activity Of Arco 2 G 2 (Snme 3 I) 4 (2) and Agnomentioning
confidence: 99%
“…On the other hand, the treatment with different drugs in the so-called combination therapy is interesting from the point of view of reducing the doses to be administered, reducing the side effects of the drugs. Related to the use different compounds in combination therapy, silver is a compound with a low toxicity that is widely used in medicine [20,21]. Different salts such as silver nitrate (AgNO 3 ), silver diamine fluoride or silver nanoparticles, among others; have a broad antibacterial and antifungal spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary mechanism of the caries-arresting effect of SDF is its microbicidal effect on cariogenic biofilm [ 26 , 27 ]. Laboratory studies have revealed the strong inhibitory effect of SDF on monospecies biofims of Sreptococcus mutans , Actinomyces naeslundii , Sreptococcus sobrinus and Lactobacillus acidophilus [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%